2021
DOI: 10.3389/fpsyg.2021.730068
|View full text |Cite
|
Sign up to set email alerts
|

The More Insufficient, the More Avoidance? Cognitive and Affective Factors that Relates to Information Behaviours in Acute Risks

Abstract: This study examines the relationship between cognitive and affective factors and people's information-seeking and -avoiding behaviours in acute risks with a 1,946-sample online survey conducted in February 2020, during the outbreak of the COVID-19 pandemic in mainland China. Multiple linear regression analysis showed that perceived information insufficiency correlates negatively with information-seeking behaviour and there was an inverted U-shaped relationship between information insufficiency and avoidance be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…Consistent with this claim, previous studies of risk-related information behavior have demonstrated a positive relationship between perceived epidemic risk and information-avoidance behavior through feelings of fear ( Jepson and Chaiken, 1990 ; Witte, 1994 ; Chiang and Tang, 2022 ). Notably, these studies mainly focused on the context of chronic risks for which people may not perceive a strong sense of urgency or prioritize acting immediately ( Zhao and Liu, 2021 ). For example, Chiang and Tang (2022) mainly focused on internet security compliance behavior in a public Wi-Fi usage condition, and demonstrated that fear was an important determinant of the user’s avoidance behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with this claim, previous studies of risk-related information behavior have demonstrated a positive relationship between perceived epidemic risk and information-avoidance behavior through feelings of fear ( Jepson and Chaiken, 1990 ; Witte, 1994 ; Chiang and Tang, 2022 ). Notably, these studies mainly focused on the context of chronic risks for which people may not perceive a strong sense of urgency or prioritize acting immediately ( Zhao and Liu, 2021 ). For example, Chiang and Tang (2022) mainly focused on internet security compliance behavior in a public Wi-Fi usage condition, and demonstrated that fear was an important determinant of the user’s avoidance behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this inference, correlational evidence in the previous studies also indicated that the levels of fear were positively associated with a sense of powerlessness in the middle of the COVID-19 pandemic ( Lifshin et al, 2020 ). In the context of COVID-19, individuals with powerlessness tended to avoid information regarding the risks when they felt a greater likelihood of being personally affected ( Chen et al, 2021 ; Zhao and Liu, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The fact that trainees feel a large proportion of their consultants are not skilled in DGBI may reflect a lack of DGBI exposure in the consultant body, consequent lack of confidence regarding management, and resultant antipathy. Studies have shown that a lack of perceived knowledge of a subject 22 or the perception of difficulty 23 can result in anxiety, reduced confidence, and avoidance. 23 Finally, almost a third of UK trainees surveyed indicated that patient attitudes and cultural beliefs were frequently a barrier to treatment.…”
Section: Barriers To Dgbi Managementmentioning
confidence: 99%
“…Studies have shown that a lack of perceived knowledge of a subject 22 or the perception of difficulty 23 can result in anxiety, reduced confidence, and avoidance. 23 Finally, almost a third of UK trainees surveyed indicated that patient attitudes and cultural beliefs were frequently a barrier to treatment. Cultural barriers have been described as adversely affecting the outcomes of patients with DGBI.…”
Section: Barriers To Dgbi Managementmentioning
confidence: 99%
“…A recent strand of the literature indicated various drivers of information seeking. Inter alia, trust and risk perception (Jin et al, 2020), information source characteristics and demographics (Desta et al, 2019), social psychological (Chang et al, 2017), cognitive and affective factors (Zhao and Liu, 2021), consumer social network (Lee, 2014), social media exposure (He and Li, 2021), social environment (Yang and Kahlor, 2013), and cognitive barriers to information seeking (Savolainen, 2015) are major ones. According to Boot and Meijman (2010), these driving factors include psychology, mass communication, library and information science, and medical science.…”
Section: Literature Reviewmentioning
confidence: 99%